PENGARUH PIRANTI FUNGSIONAL LEPASAN TERHADAP PERUBAHAN PANJANG MANDIBULA - Yufridika, Erna Sulistyawati, Muslim Yusuf (ODONTO : Dental Journal, 2018)
Background: Class II malocclusion prevalence is about 70%. Class II malocclusion could be caused by retrognatic mandible and normal maxilla, prognatic maxilla and normal mandible or combination of retrognatic mandible and prognatic maxilla. Class II malocclusion can be treated with fixed or removable functional appliance on advancing mandibular length. Aim: To examine the effect of functional appliance in mandibular length. Method: Age of sample is ranging from 7-13 years old treated using removable functional appliance with proper and complete medical record. In this research, a purposive sampling method was used. The mandibular length changes of samples were evaluated and analyzed with statistical computerized system. Result: The research reveals that total mandibular length was changed by 7.09 mm while mandibular corpus length was changed by 3.27 mm. Based on paired t-test, these results are found to be statistically significant (p< 0.05). Conclusion: The removable functional appliance on samples with Class II malocclusion contributes a significant effect both for total mandibular and corpus mandibular length.